2020
DOI: 10.1002/cbdv.202000810
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Mechanism of Guchang Zhixie Wan for Treating Ulcerative Colitis by Comprehensive Network Pharmacological Approaches and Molecular Docking Validation as Well as Cell Experiments

Abstract: Guchang Zhixie Wan (GZW) is a commonly used Chinese medicine for the treatment of ulcerative colitis (UC). This research explored the potential pharmacological mechanism of GZW in UC. The active ingredients, potential targets, and UC-related genes of GZW were retrieved from public databases. The pharmacological mechanisms including key components, potential targets and signal pathways were determined through bioinformatics analysis. The results of this study were verified through virtual molecular docking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The GeneCards, OMIM, DrugBank, and PharmGKB databases were searched for relevant gene targets using the keyword “ulcerative colitis,” as shown in previous studies [ 4 ]. These potential XJD target genes were then linked to UC target genes to identify candidate targets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GeneCards, OMIM, DrugBank, and PharmGKB databases were searched for relevant gene targets using the keyword “ulcerative colitis,” as shown in previous studies [ 4 ]. These potential XJD target genes were then linked to UC target genes to identify candidate targets.…”
Section: Methodsmentioning
confidence: 99%
“…Aminosalicylic acid preparations, commonly used in the treatment of UC, exert anti-inflammatory effects mainly by affecting the metabolism of arachidonic acid and inhibiting prostaglandin synthesis, but their adverse effects are more frequent and their therapeutic effects are less satisfactory. Traditional Chinese medicine (TCM) has been shown to have potential advantages in UC treatment [ 1 , 4 , 5 ]. Hu et al recently found that XJD was effective in treating UC by effectively regulating neuroendocrine factors, improving the intestinal immune response, and reducing patient symptoms [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As described in previous studies, we molecularly docked the screened core active ingredient to the core protein to verify the interaction strength ( 43 ). The active ingredient structures were obtained from the PubChem database and the protein structures were obtained from the Protein Data Bank (PDB) ( 44 , 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…(3) The pathway enrichment analysis of single cells was performed using the Single-Cell Signature Explorer, and the expression abundance of the target pathway is calculated. (4) GO and KEGG enrichment analyses are widely used research methods; they are conducted using the clusterProfiler package (version 3.14.3), and the org.Mm.eg.db package (version 3.10.0) was used for ID transformation [ 59 , 62 , 63 ].…”
Section: Methodsmentioning
confidence: 99%